Green sustainable process for chemical and environmental engineering and science : green solvents for environmental remediation - Inamuddin, 1980-; Boddula, Rajender; Asiri, Abdullah M. (Elsevier, 2021)
Green Solvents for Environmental Remediation provides an in-depth overview of environmental remediation by using eutectic solvents, ionic liquids, biosolvents, and switchable solvents, of ionic-liquids, biosolvents, Gas-expanded solvents Liquid polymers, supercritical fluids, Polymer-based green solvents, Switchable solvents, etc. This book offers all-types of green solvents for the removal of contaminations from the soil, air, and water. It summarizes in-depth literature on the application of various green solvents in the areas such as municipal water, extraction, bioremediation, phytoremediation, soil and sediment remediation, toxic gases removal, and various industrial effluents. A brief introduction, limitations, and advantages to the practical use of green solvents are also discussed. This book is authored by experts in a broad range of fields. It is an invaluable reference guide for the sustainable and environmentally friendly development of synthetic methodologies for environmental, analytical, engineering, and industrial technology.